Effectiveness of cognitive-behavioral group therapy in quality of life and hope among patients with multiple sclerosis - Shareh, Hossein; Robati, Zahra (Researcher Bulletin of Medical Sciences, 2019)
Introduction: The present study was aimed at investigating the effectiveness of cognitive-behavioral group therapy in quality of life and hope among patients with multiple sclerosis (MS). Materials and Methods: In this clinical trial, using a quasi-experimental pretest-posttest control group design, 20 MS patients were selected through available sampling among the patients in Mashhad Multiple Sclerosis Association in 2016 and were randomly assigned into two experimental and control groups, each containing 10 subjects. The experimental group underwent cognitive-behavioral group therapy in 10 weekly sessions of 2 hours and the control group did not receive this treatment. In the pretest and posttest, Quality of Life Questionnaire-Short Form (SF-36) and Snyder ‎Adult Hope Scale (AHS)‎ were implemented on all the subjects of the experimental and control groups. Data was analyzed using analysis of covariance and t-test. Results: The results demonstrated that cognitive-behavioral group therapy significantly leads to increased overall index of quality of life and hope (p<0.001) in the experimental group compared to the control group. Further, out of quality of life components, dimensions of physical function, role limitation due to physical problems, fatigue or vitality, emotional health and general health of the experimental group showed a greater increase at the end of the intervention relative to the control group (p<0.001) and concerning other subscales, the difference between the two groups was not significant.